Droughts and floods in Malawi: Assessing the economywide effects - Pauw, Karl; Thurlow, James; van Seventer, Dirk (International Food Policy Research Institute, 2010)
Malawi suffers frequent droughts and floods. In an economy that is heavily dependent on the agricultural sector, it is crucial to understand the implications of these extreme climate events. Not only are rural livelihoods affected due to the severe impacts on the agricultural sector, but nonfarm and urban households are also vulnerable given the strong production and price linkages between agriculture and the rest of the economy. This study uses a general equilibrium model to estimate the economywide impacts of drought- and flood-related crop production losses. Climate simulations are based on production loss estimates from stochastic drought and flood models. Model results show that the economic losses due to extreme climate events are significant: Malawi loses 1.7 percent of its gross domestic product on average every year due to the combined effects of droughts and floods. This is equivalent to almost US$22 million in 2005 prices. Given their crop choices, it is smaller-scale farmers and those in the flood-prone southern regions of the country who are worst affected. However, urban and nonfarm households are not spared. Food shortages lead to sharp price increases that reduce urban households' disposable incomes. This study makes an important contribution by estimating the economywide impacts of extreme climate events. However, this is only the first step toward designing appropriate agricultural and development strategies that explicitly account for climate uncertainty.